More than Empty Plates: Assessing the Factors behind Food Insecurity in the Philippines - Velasco, Francine Isabel; Magpantay, Ederliza (Faculty of Science and Technology University of Pramita Indonesia, 2024)
Food insecurity has been a long-standing challenge in the Philippines, where one must allocate a budget for a decent and sufficient daily meal. This study aims to assess the factors behind food insecurity in the Philippines and their extent using regional data from the years 2015, 2018, and 2021. The panel quantile regression analysis was utilized to determine and assess the economic factors affecting food insecurity. The researcher was also able to gauge which regions have the least, moderate, and high prevalence of food insecurity using the 25th, 50th, and 75th quantiles of the dependent variable, respectively. Using the percentile scores in data distribution, the National Capital Region, Region III (Central Luzon), and Region IVA (CALABARZON) are regions with the least prevalence of food insecurity. The regions with a moderate prevalence of food insecurity are Region IVB (MIMAROPA), Region VI (Western Visayas), and Region XI (Davao). On the other hand, regions with a high prevalence of food insecurity are Region IX (Zamboanga Peninsula) and Bangsamoro Autonomous Region in Muslim Mindanao. Other regions were determined to have experienced different levels of prevalence of food insecurity in different years. The quantile regression results revealed that poverty incidence and economic growth have a significant positive relationship, and the minimum wage has a significant negative relationship with food insecurity across all levels of food insecurity prevalence by region. The consumer price index of food was found to be a statistically significant factor and is positively correlated with food insecurity only in regions where food insecurity is highly prevalent. It is also an insignificant factor in regions with the least and moderate prevalence of food insecurity.